Bacillus subtilis Improves Immunity and Disease Resistance in Rabbits - Guo, Mengjiao; Wu, Fahao; Hao, Guangen; Qi, Qin; Li, Rong; Li, Ning; Wei, Liangmeng; Chai, Tongjie (Frontiers in Immunology, 2017)
Probiotics such as Lactobacillus and Bifidobacterium have been successfully used to promote growth and prevent diseases. Previous reports have demonstrated that Bacillus subtilis (B. subtilis) was a potential probiotic for animals. In this research, 180 B. subtilis were isolated from the soil, identified, and investigated in vitro. Furthermore, five B. subtilis were selected and mixed to investigate their effect on growth performance, immune response, intestine microbiota, and disease resistance in rabbits. Rabbits with a diet of 106 CFU g−1 mixed B. subtilis exhibited the best growth performance and higher serum IgG and IgA than controls (P < 0.05). Moreover, dairy with B. subtilis can promote the balance of intestinal flora. The major proinflammatory factor and β-defensin were upregulated compared with the controls. After 7 weeks of feeding, the survival rate of the rabbits fed with B. subtilis was significantly higher than those in the control groups postinfected with Escherichia coli. At the same time, this study detected higher expression of β-defensin and reduced bacteria contents of the heart and cecal contents from the diet mixed with B. subtilis compared with the control groups. In conclusion, dietary supplementation with B. subtilis for rabbits could improve growth performance, intestinal homeostasis, and immune organ index and enhance innate immune response as well as disease resistance. These findings showed that the induction of β-defensin by B. subtilis might be an interesting new therapeutic strategy to strengthen innate defense mechanisms.